The Peanuts movie - Martino, Steve, 1959-; Schulz, Craig; Schulz, Bryan; Uliano, Cornelius, 1985-; Schnapp, Noah; Melendez, Bill; Miller, Hadley Belle; Andrews, Troy; Bloom, Rebecca; Bredikhina, Anastasia; Garfin, Alex; Beck, Christophe, 1972-; et al. (Beverly Hills, California Twentieth Century Fox Home Entertainment, 2016)
Charlie Brown, the world's most beloved underdog, embarks upon an epic and heroic quest, while his best pal, the lovable beagle Snoopy, takes to the skies to pursue his arch-nemesis, the Red Baron. Charlie Brown, Snoopy, Lucy, Linus, and the rest of the beloved Peanuts gang make their big-screen debut, like they've never been seen before, in state-of-the-art animation.
Special features: 6 Snoopy snippets; "Better when I'm dancin'" Megan Trainor music & lyric videos; learn to draw Snoopy, Woodstock and Charlie Brown; Get down with Snoopy and Woodstock music video; behind the scenes of "Better when I'm dancin'"; Snoopy's playlist.
Based on the comic strip by Charles M. Schulz.
Originally released as a motion picture in 2015.
Widescreen (1.85:1).
Special features: 6 Snoopy snippets; "Better when I'm dancin'" Megan Trainor music & lyric videos; learn to draw Snoopy, Woodstock and Charlie Brown; Get down with Snoopy and Woodstock music video; behind the scenes of "Better when I'm dancin'"; Snoopy's playlist; gallery; trailers.
Music, Christophe Beck ; editor, Randy Trager ; art director, Nash Dunnigan ; supervising animators, Nick Bruno, Scott Carroll ; cinematographer, Renato Falcao.
Voice actors: Noah Schnapp, Bill Melendez, Hadley Belle Miller, Troy "Trombone Shorty" Andrews, Rebecca Bloom, Anastasia Bredikhina, Alex Garfin, Mariel Sheets, Kristin Chenoweth.
Keywords: Brown, Charlie -- (Fictitious character) -- Juvenile films; Snoopy -- (Fictitious character) -- Juvenile films; Schulz, Charles M. -- 1922-2000.; Friendship -- Juvenile films; Brown, Charlie (Fictitious character) -- Drama; Snoopy (Fictitious character) -- Drama; Feature films; Animated films; Children's films; Friendship -- Videorecordings; Quests -- Videorecordings; Fiction films; Film adaptations; Computer animation films; Comedy films; Animated films; Children's films; Juvenile works; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Animated films; Feature films